Students' musical preferences in childrens' major- and minor-key songs - Dobrota, Snježana (Revija za elementarno izobraževanje, 2020)
This paper explores elementary school students' music preferences in terms of songs authored for children and traditional major- and minor-key songs and the influence of familiarity of the music on their music preferences. The questionnaire and sound questionnaire were administered to 216 students attending the second, third, seventh and eighth grades of elementary school in Sinj, Croatia. The results confirm the influence of age and gender on students' music preferences concerning songs authored for children and traditional songs in major and minor keys. Furthermore, all the participants prefer major-key songs to minor-key songs. Finally, it was established that familiarity with a piece of music is a significant factor affecting the music preferences of the participants.
Keywords: children's songs; dur; glasbene preference; major mode; minor mode; mol; music lessons; otroške pesmi; pouk glasbe; preference